Hidden work, frustration and multiple layers of occupational health in emergency situations: a longitudinal study during the COVID-19 pandemic - Černe, Matej; Aleksić, Darija (Frontiers in Psychology, 2024)
This study examines the effects of the COVID-19 pandemic over time. Specifically, we derive from the organisational model of frustration to propose and test a model of pandemicinduced hidden work affecting employees' emotional responses of frustration along with behavioural responses and outcomes with respect to occupational health. We thereby develop a concept of multiple layers of occupational health that spans across stress, satisfaction with work-life balance (SWLB), burnout, subjective well-being, and physical health. Based on a longitudinal web-based survey of 198 working professionals conducted at seven points in time (1,143 data points, with 118 fully completed responses across all time points) for a wide range of industries in 2020, the study tests the proposed relationships using random coefficient modelling. The results show that COVID-19-situation-induced hidden work invokes emotional responses of frustration, which in turn influence outcomes referring to multiple layers of occupational healthpositively affecting stress and burnout, and negatively influencing SWLB, subjective well-being, and physical health. Implications for research and practice are discussed.